La conduite en état d’ébriété : les impacts des modifications législatives de décembre 1985 tels que perçus par les policiers - Beaulieu, Marie (Criminologie, 1989)
Did the legislative changes of December 1985 concerning impaired driving affect the work of the penal agents? The author answers this question on the basis of interviews with peace officers of the various police corps of Greater Montreal. The Act did change their attitudes as well as their methods of enforcing the legislation. There was also a change in their personal and professional attitudes toward drunken driving. The police say they had noted variations in the attitudes and behaviour of the general public.